(3MeGjI GdefGWb HGJaGb GdCWQGa GdeJfGRYI CKfGA GdfRGYGJ GdeSdMI GdOhdjIs - (3GdajGV(B, (3fbGA KGHJ VGQjs ((3GdGScfOQjIs (3GdecJH GdLGeYj GdMOjKs, 2022)
(3eGgjI GdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI, JYQja GdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI, JejjR GdefGWb GdeMejI HGJaGb CWQGa GdfRGY YeG JTJHg HgG, GdCSGS GdbGfhfj dEbGeI GdefGWb GdeMejI HGJaGb CWQGa GdfRGY, CMcGe MeGjI GdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI, MeGjI efGWb GdGSJTaGA hGdCeGf hGdefGWb GdeMGjOI HGJaGb GdCWQGa GdeJfGRYI, MeGjI GdefGWb GdeLQOI ef hSGFd GdOaGY hGdefGWb GdefRhYI GdSdGM HGJaGb GdCWQGa GdeJfGRYI, GdeSDhdjI Yf GdCVQGQ HGdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI, GdWHjYI GdbGfhfjI ddeSDhdjI GdOhdjI Yf GdCVQGQ HGdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI, GdBKGQ GdbGfhfjI ddeSDhdjI GdOhdjI Yf GdCVQGQ HGdefGWb GdeMejI HGJaGb GdCWQGa GdeJfGRYI(B.s
Keywords: (3GdefGRYGJ GdOhdjIs; (3GdefGWb efRhYI GdSdGMs; (3fRY GdSdGMs